THE INFLUENCE OF WHIP AROUND TECHNIQUE TOWARD WRITING DESCRIPTIVE PARAGRAPH OF THE TENTH GRADE STUDENTS OF STATE SENIORHIGH SCHOOL 4 OF PALEMBANG - Herlina Herlina; Asti Veto Mortini; Ria Pratama (Universitas PGRI Palembang, 2020)
The objective of this study was to find out whether or not there is any significant influenceon student’s achievement in writing descriptive paragraph tothe tenth grade students of State Senior High School 4 Palembang who are taught through Whip Around Technique and those who are not. Thi study applied quasi-experiment method with nonequivalent control group design. The population of this study was all of the tenth grade students of State Senior High School 4 of Palembang, in the Academic Year 2018/2019 with total number 320 students and 64 students were taken as sample in experimental and control group. In collecting the data, a written test of descriptive paragraph was used, and the data were analyzed by using SPSS 22. The result of this study showed that experimental group students’ average score in pretest was 64.37 and in posttest it was 77.93 while in control group, students’ average score in pretest was 64.53 and in posttest it was 66.78. The value t-obtained was (11.392) which was higher than the value of t-table (2.000) at the significant level 0.05 in two tailed test with 62 (df). It was assumed that the null hypothesis (H0) was rejected, and the alternative hypothesis (Ha) was accepted. It means that there was significant influenceon student’s achievement in writing descriptive paragraph tothe tenth grade students of State Senior High School 4of Palembang who were taught through Whip Around Technique. Keywords: Teaching, Writing, Descriptive Text, Whip Around